Light-induced electric dipole relaxation in synthetic and natural alexandrite - Scalvi, Rosa Maria Fernandes [UNESP]; Siu Li, M.; Ruggiero, Ligia de Oliveira [UNESP]; Scalvi, Luis Vicente de Andrade [UNESP] (Taylor & Francis, 2002)
We present results of thermally stimulated depolarization current (TSDC) measurements in synthetic and natural alexandrite, which show TSDC bands related to the presence of electric dipoles in both types of samples. Synthetic material shows a wide TSDC band with a peak at 179 K, which can be fitted by two distinct relaxing dipole distributions. For natural alexandrite the TSDC band has a maximum around 195 K and can be fitted by three different distributions. Both samples present one of the calculated curves with a peak about 179 K, with activation energy of 0.57 eV and constant relaxation time of 1 × 10-14 sec. Photo-induced TSDC shows that TSDC bands can also be generated by simultaneous application of light and an electric field at 77 K.
Keywords: Alexandrite; Depolarization current; Dipole relaxation; Electrical properties